Plotting the major proteins of borealpox virus - Thomas, Sunil (Frontiers in Virology, 2024)
In an era marked by rapid environmental transformations, the viability of numerous species hinges crucially on their ability to navigate and adjust to shifting climatic conditions through migration. Yet, amidst this natural quest for survival, a consequential and often overlooked consequence emerges: the inadvertent transportation of a diverse array of parasites and pathogens across landscapes. This phenomenon poses a substantial and tangible threat to global health, particularly in the wake of recent outbreaks and pandemics fueled by zoonotic viruses, which leap from animals to humans. These viruses, originating in animals but capable of infecting humans, serve as poignant reminders of the intricate relationship between human and wildlife health, and the potential dangers of disregarding this delicate balance. In 2015, the borealpox virus (BRPV) [formerly Alaskapox virus (AKPV)], classified as an Orthopoxvirus, was first identified in a woman living near Fairbanks, Alaska. The BRPV causes borealpox disease. The first recorded fatality attributed to BRPV infection occurred in January 2024. Current evidence suggests that BRPV primarily targets small mammals, particularly red-backed voles and shrews, as evidenced by sampling efforts in the Fairbanks North Star Borough. However, it is likely that the virus is more widespread among Alaska’s small mammal populations, potentially leading to undiagnosed human infections. Additionally, domestic pets, such as cats and dogs, may also contribute to the transmission of the virus. To date, no instances of human-to-human transmission have been documented, but the lack of diagnostics and vaccines for BRPV remains a concerning gap. This paper aims to address this issue by reporting the structure and epitopes of the major proteins of BRPV. This data could serve as a foundation for the development of novel diagnostics and vaccines to combat BRPV, thereby mitigating its impact on both human and animal populations.